On the estimation of the strange quark mass from the experimental data on the light baryon octet - V. A. Babenko; N. M. Petrov (Ядерна фізика та енергетика)
Simple relations connecting the strange quark mass to the splittings of the light hyperon masses were obtained on the basis of the phenomenological quark model compatible with the present-day theory of strong interactions, i.e. with quantum chromodynamics (QCD). Strange quark mass ms = 89.5 ±19.5 MeV, calculated in the proposed approach, is in good agreement with the modern evaluations and calculations of this quantity, mainly obtained by the lattice QCD methods.